Hurricane Dennis' Impact on Cuban Agriculture - William A. Messina, Jr.; Thomas H. Spreen (EDIS)
Between July 7 and July 9, 2005, Hurricane Dennis moved along the southern coast of Cuba then moved across the island, enveloping nearly the entire country with strong hurricane and tropical storm force winds and driving rain. This was the fourth major hurricane to strike Cuba in the last four years. As a Category 4 storm on the Saffir-Simpson Hurricane Scale when it came ashore in central Cuba on July 8, Hurricane Dennis brought with it sustained winds reported at nearly 150 mph (240 kph) and wind gusts as high as 155 mph (250 kph), making it the strongest hurricane to strike Cuba in four decades (Havana Journal, July 10, 2005). This is EDIS document FE570, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published August 2005.